An Improved N-Acylation of 1H-Benzotriazole Using 2,2′-Dipyridyldisulfide and Triphenylphosphine - Singh, Anoop S.; Agrahari, Anand K.; Mishra, Nidhi; Singh, Mala; Tiwari, Vinod K. (Synthesis, 2019)
A novel path has been developed for the conversion of carboxylic acids into the corresponding N-acylbenzotriazoles by using 2,2′-dipyridyl disulfide/PPh3 in anhydrous dichloromethane in the presence of 1H-benzotriazole. Mild reaction conditions, short reaction time, easy in handling, wide substrate scope, availability of reagents involved, and moreover avoiding the use of base makes this protocol quite useful for the laboratory practices for N-acylbenzotriazole synthesis.
Keywords: N-acylbenzotriazole; coupling reaction; PPh3; PySSPy